Enhancing retention of information through postretrieval negatively arousing stimuli. - Lim, Yvonne ShiYing. (2013)
Many studies have shown how emotions aid or impair memory during the encoding stage. Fewer studies have focused on this relationship during retrieval. This paper explores how inducing emotional arousal following retrieval affects performance on cued recall and recognition tests. Specifically, this study is an extension of previous experiments in this area and it manipulates the materials used (passages, cued recall and recognition tests), method (1 week retention interval) and paradigm (balanced design) to provide more ecological validity. Twenty undergraduates from Nanyang Technological University took part into in the study. They were randomly allocated into 2 groups – negative and positive postretrieval condition. Each participant had to go through both an emotional arousal and neutral (control)